Utilizing Dataisland to Create Interactive Maritime English Exercises - Yurzhenko, Alona; Diahyleva, Olena; Kononova, Olena (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The paper is devoted to the use of new platform to secure, process and store data (Dataisland). The advantages of using Dataisland are listed in the research. It is highlighted that the platform helps Maritime English teachers to develop interactive exercises which could be useful to form communicative competence of future seafarers. Strong security measures are provided to protect created content, the updates are periodical.